Efektifitas Kompres Hangat Jahe Merah Dan Kompres Hangat Rebusan Serai Terhadap Penurunan Nyeri Sendi Pada Lansia Penderita Arthritis Gout Di Wilayah Puskesmas Gandus Tahun 2025 - Pranata, Rama; Utama Saputra, Andre; Harisandy, Alvian (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Gout arthritis is a degenerative disease frequently found in the elderly, characterized by joint pain caused by uric acid crystal deposits. Pain management can be achieved through pharmacological and non-pharmacological approaches, including herbal warm compresses. This study aimed to evaluate the effectiveness of warm red ginger compresses (Zingiber officinale Roscoe var. rubrum) and warm lemongrass decoction compresses (Cymbopogon citratus) in reducing joint pain among elderly patients with gout arthritis at the Gandus Public Health Center, Palembang, in 2025. A quasi-experimental design with a pretest–posttest two-group approach was applied. Thirty elderly respondents were recruited using total sampling and divided into two intervention groups. Pain intensity was measured using the Numerical Rating Scale (NRS), and data were analyzed with the Wilcoxon and Mann-Whitney tests. The results showed that both warm red ginger and lemongrass compresses significantly reduced joint pain (p = 0.000), but no significant difference was found between the two interventions (p = 0.550). These findings confirm that both therapies are equally effective in relieving joint pain in elderly patients. Therefore, warm compresses with red ginger or lemongrass can be recommended as safe, simple, effective, and practical non-pharmacological alternatives for managing gout arthritis pain in older adults.